(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Objective: to identify the histological features in the limbal-cornealzone in experimental animals at different periods of the experiment, after modeling degenerative and proliferative process associated with the growth of the conjunctiva to the cornea, as close as possible to clinical manifestations of pterygium. Results: In an experiment on 28 eyes of 14 rabbit’s chinchilla studied pathological features of development of limbal insufficiency in different terms modeling degenerative and proliferative process.